Effect of eating liquorice on the renin-angiotensin aldosterone axis in normal subjects. Issue 6059 (19th February 1977) - Epstein, M T; Espiner, E A; Donald, R A; Hughes, H
Abstract : The effect of confectionery liquorice on electrolyte status and the renin-angiotensin-aldosterone (RAA) axis was studied in 14 healthy volunteers. They ate liquorice in daily doses of 100 g or 200 g (equivalent to 0-7-1-4 g glycyrrhizinic acid) for one to four weeks. Plasma potassium concentrations fell by over 0-3 mmol/l in 11 people, including four who had to be withdrawn from the study because of hypokalaemia. One or more values of the RAA axis, especially plasma renin activity and urinary aldosterone concentrations, were considerably depressed in all subjects. These results show that potentially serious metabolic effects may occur in some people who eat modest amounts of liquorice daily for less than a week.